1992
DOI: 10.1007/bf01253108
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the different binding sites of the N-methyl-D-aspartate (NMDA) receptor to the expression of behavior

Abstract: The effects of competitive (CGP 37849 and CGP 39551) and non-competitive (dizocilpine) N-methyl-D-aspartate (NMDA) antagonists were tested in three animal models (catalepsy, sniffing, locomotion) and, in addition, the modulation of these effects by an agonist of the strychnine-insensitive glycine binding site was investigated. Both competitive and non-competitive NMDA antagonists reduced neuroleptic-induced catalepsy. Weak sniffing was induced by the competitive antagonist but strong sniffing by the non-compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
2

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 53 publications
(51 reference statements)
4
34
2
Order By: Relevance
“…If the present hyperactivity model, achieved by combined NMDA receptor antagonism and a 2-adrenoceptor stimulation, has any relevance for psychosis, the prediction based on the present results would be that D-cycloserine, contrary to current hopes (Deutsch et al, 1989;Tamminga et al, 1992; however, see also Kretschmer et al, 1992) might not be so effective in schizophrenia, whereas (+)-HA-966, as previously suggested by Reynolds (1992), might be an interesting candidate. In line with this notion it has been reported that glycinergic agonists actually can worsen schizophrenic symptomatology (Simeon etal., 1970;Rosse etal., 1990;Cascella N, personal communication).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…If the present hyperactivity model, achieved by combined NMDA receptor antagonism and a 2-adrenoceptor stimulation, has any relevance for psychosis, the prediction based on the present results would be that D-cycloserine, contrary to current hopes (Deutsch et al, 1989;Tamminga et al, 1992; however, see also Kretschmer et al, 1992) might not be so effective in schizophrenia, whereas (+)-HA-966, as previously suggested by Reynolds (1992), might be an interesting candidate. In line with this notion it has been reported that glycinergic agonists actually can worsen schizophrenic symptomatology (Simeon etal., 1970;Rosse etal., 1990;Cascella N, personal communication).…”
Section: Discussioncontrasting
confidence: 57%
“…In electrophysiological and in vitro binding studies MK-801 and other PCP-like compounds have been found to display so-called agonist-or use-dependency (see Reynolds and Miller, 1988;Lodge and Johnson, 1990;Wong etal., 1991), i.e., they can reach their binding sites within the channel when in its open state and exert a blocking action only in the presence of agonist; concurrent stimulation of the glutamate and the glycine site appears to be a prerequisite (Kloog etal., 1990;Wong etal., 1991). In vivo studies aimed at further elucidating this phenomenon observed in vitro are scarce (see, however, Raffa et al, 1989;Kretschmer et al, 1992). Therefore, the following study was undertaken with the purpose of clarifying how ligands acting on the glutamate site, the glycine site and the PCP site interact in an vivo behavioral model.…”
Section: Introductionmentioning
confidence: 99%
“…Antagonism towards the neurolepticinduced catalepsy in rats is also evoked by memantine (Maj et af., 1974;Schmidt et af., 1991), another non-competitive NMDA receptor antagonist (Bormann, 1989). The haloperidol-induced catalepsy in rats is also reduced by the competitive NMDA receptor antagonists CGP 37849, CGP 39551 and CPP-ene (Schmidt et af., 1991;Kretschmer et al, 1992). As we demonstrated previously, CGP 37849, and to a lesser extent-CGP 39551, antagonize the spiperone-and ff uphenazine-induced catalepsy in rats (Maj et a/., 1993b).…”
Section: Introductionsupporting
confidence: 68%
“…On the other hand, a reduced burst firing might cause a reduced dopamine activity with disorders of attention and motivation. Furthermore, Kretschmer et al, (1992) demonstrated that dizocilpine (M < 801) induced sniffing and locomotion were enhanced by D-cycloserine rather than inhibited.…”
Section: Introductionmentioning
confidence: 97%